The perception of graphic design students on Mr.Keli’s product on their busy lifestyle / Fatimah Widadi Md. Nurdin - Md.Nurdin, Fatimah Widadi (2011)
Therefore, the objective of this study is to find out the Graphic Design students’ perception of Mr.Keli’s effects on their busy lifestyle. The finding shows the perception of Graphic Design students on how Mr.Keli product would give effects on their busy lifestyle. It is recommended for Graphic Deisgn students to eat Mr.Keli product during their busy moment to live healthier as a student. This academic writing consisted of four chapters. This includes background of research, objectives and research methodology, analysis and findings and last but not least conclusion and recommendation. In the background of research it focused on the overview of overall research that has been made by previous study. In the objective and research methodology section is consisted of the description of methods, techniques throughout the research by qualitative method. This section will describe and explain in detail of how the survey going to be conducted.